Perjuangan Tokoh Utama Menuju Superioritas Dalam Novel Adiba Karya Mairisa Elvia : Kajian Psikologi Individual Alfred Adler - Muhitotun Nadhifah; Wawan Hermawan; Engkin Suwandana (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze the struggle of the main character in achieving superiority in the novel Adiba by Mairisa Elvia. This struggle is rooted in the feelings of inferiority experienced by the main character since childhood. Through the individual psychology approach of Alfred Adler and qualitative descriptive methods, this research reveals the forms of the character's struggle in responding to traumatic experiences, social pressures, and inner conflicts that affect the direction of her life. Data were collected from quotes of narration, dialogue, or actions of the characters in the novel that reflect the effort to overcome feelings of helplessness and achieve meaningful life goals. Data collection techniques were conducted through careful reading and systematic note-taking of relevant parts of the text. The data were analyzed using content analysis to unveil the meanings behind actions, dialogues, and narratives related to the dynamics of the character's struggle. The research results show that the struggle towards superiority is demonstrated through hard work, a never-give-up attitude, and a drive to be beneficial to others. The main character not only struggles to overcome personal weaknesses but also shows a transformation of personality through constructive and social achievements. This process reflects an individual's journey in shaping a lifestyle and ultimate goals as compensation for the feelings of inferiority they once experienced. This study concludes that the psychological aspects in literary works can provide a deeper understanding of the motivations and personality dynamics of the characters, as well as enrich literary analysis with an interdisciplinary approach.